2013
DOI: 10.1055/s-0033-1335937
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Evaluation of the Influence of Iterative Reconstruction and Filter Kernel on Subjective and Objective Image Quality in Computed Tomography of the Brain

Abstract: Objectives: To intraindividually evaluate the potential of 4th generation iterative reconstruction (IR) on brain CT with regard to subjective and objective image quality. Methods: 31 consecutive raw data sets of clinical routine native sequential brain CT scans were reconstructed with IR level 0 (=?filtered back projection), 1, 3 and 4; 3 different brain filter kernels (smooth/standard/sharp) were applied respectively. Five independent radiologists with different levels of experience performed subjective imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
(9 reference statements)
2
7
0
Order By: Relevance
“…The current research findings support a preference for low iteration strengths as reported in some abdominal and cranial studies [29][30][31]. Numerous other authors [1,6,27,[32][33][34][35] report the use of higher iteration strengths without loss of demarcation across multiple anatomic areas. There may be a number of reasons for opinion variation including the CT system used, the Table 2 for exposure protocol and image randomization numbers.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The current research findings support a preference for low iteration strengths as reported in some abdominal and cranial studies [29][30][31]. Numerous other authors [1,6,27,[32][33][34][35] report the use of higher iteration strengths without loss of demarcation across multiple anatomic areas. There may be a number of reasons for opinion variation including the CT system used, the Table 2 for exposure protocol and image randomization numbers.…”
Section: Discussionsupporting
confidence: 84%
“…Significant differences in scores for diagnostic acceptability, lesion conspicuity, and total diagnostic ability were evident between optimized protocols but not for diagnostic confidence in pathology visualization. Unlike previous studies [6,9,15,21], significant differences were only seen when full-dose and reduced-dose FBP protocols were compared. This finding was not evident in the comparison of lower dose IR and FBP protocols, possibly due to the use of optimized low IR strengths in this study with resultant minimal alterations in noise patterns.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The ability to distinguish between noise and structures obviously diminishes with increasing IR strength when structures and differences in density become small. This has already been reported in a number of other studies, assessing iterative reconstruction algorithms of various vendors [3941]. As a consequence the edges of the filling defects become diffuse with IMR, making it difficult to resolve small structures as small subsegmental emboli, even though the overall image noise is remarkably decreased by IMR.…”
Section: Discussionmentioning
confidence: 74%